(untitled) (International Journal of Engineering and Computer Science, 2017)
Multiband OFDM based Ultra Wideband (UWB) system combines OFDM modulation technique with a multi banding approach, which divides the spectrum into several sub-bands, whose bandwidth is approximately 500MHz in order to meet with FCC requirements. This approach of multibanding introduces orthogonality in the frequency domain and also longer impulse radio pulses in each band are obtained. OFDM based system is very sensitive to timing and frequency offsets, the received constellation is slightly different from transmitted constellation due to processing delay and additional delay introduced from the channel. So Multiband-OFDM (MB-OFDM) is one of the promising candidates for short-range high data-rate UWB communications. It combines Orthogonal Frequency Division Multiplexing (OFDM) with the multi-band approach enabling UWB transmission to inherit all the strength of OFDM technique which has already been proven for wireless communications. In this paper overview of OFDM is discussed and UWB-OFDM system is studied and analyzed